Effects of conditioning activity mode, rest interval and effort to pause ratio on post-activation performance enhancement in taekwondo: a randomized study - Ouergui, Ibrahim; Delleli, Slaheddine; Messaoudi, Hamdi; Bridge, Craig Alan; Chtourou, Hamdi; Franchini, Emerson; Ardigò, Luca Paolo (Frontiers in Physiology, 2023)
The present study assessed the effects of conditioning activities, using different effortto-pause ratios and rest intervals, on taekwondo physical performance.Methods: Twenty-one athletes (13 males and 8 females) (Mean±SD; age= 20.4±1.4 years) performed a control (CC) and twelve experimental conditions. Each condition contained a standard warm-up (i.e., CC: running at 9km/h for 10min) and conditioning activities comprising plyometrics (P) or repeated high-intensity techniques (RT) using 1:6, 1:9 and self-selected rest (SSR) ratios, and two rest intervals (3 and 7min). Athletes then performed a battery of fitness tests: countermovement This is a provisional file, not the final typeset article jump (CMJ), taekwondo specific agility (TSAT), 10s and multiple frequency speed kick test (FSKT-10s and FSKT-mult, respectively).Results: All of the preloads provided higher performance outputs compared to the control trial (all p<0.05). For CMJ, 1:6 ratio with 3min induced lower values with RT compared to P (p= 0.037) and 1:9 ratio using 3min induced higher values with RT compared to P (p= 0.027). Additionally, 1:6 ratio using 7min induced higher values with RT compared to P (p= 0.016). For FSKT-10, 3min using 1:6 induced higher values with P compared to RT, while RT induced higher values with 7min using 1:6 ratio compared to P (both p<0.001). Moreover, 3min using 1:9 ratio induced higher values with P compared to RT (p=0.034), while RT induced higher values with 1:9 ratio using 7min compared to P (p<0.001). Finally, 3min using SSR ratio induced higher values with RT compared to P (p=0.034).Plyometrics and RT activities improved performance with plyometrics requiring shorter rest interval to induce potentiation effects compared to RT, which required longer interval.